1989
DOI: 10.1136/pgmj.65.770.913
|View full text |Cite
|
Sign up to set email alerts
|

Audit of mortality in upper gastrointestinal bleeding

Abstract: Summary:The outcome in 1017 patients with haematemesis and malaena referred to two major hospitals in Nottingham within a 2-year period has been prospectively evaluated. Ninety one (9%) patients died during the time period under consideration and all but four were found to have been over 60 years of age. There were 13 (14%) deaths following rebleeding, of whom 5 (5%) could have been potentially avoided by alterations in management. Some improvement of mortality might result from intensive-care facilities with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
3
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 12 publications
1
21
3
1
Order By: Relevance
“…In addition, this study provides an estimate of the risks associated with patient self-medication in peptic ulcer disease and suggests that the associated symptoms may be more prevalent than previously recognized. The patients examined in the present study appear to be representative of a wider population since the mortality associated with peptic ulcer haemorrhage was similar to that recently reported in a large district general hospital (Katschinski et al, 1989). However, in the study conducted by Katschinski and co-workers (1989) the observed mortality of approximately 10% associated with peptic ulcer haemorrhage fell to about 5% when only death directly associated with bleeding was considered.…”
Section: Discussioncontrasting
confidence: 37%
See 1 more Smart Citation
“…In addition, this study provides an estimate of the risks associated with patient self-medication in peptic ulcer disease and suggests that the associated symptoms may be more prevalent than previously recognized. The patients examined in the present study appear to be representative of a wider population since the mortality associated with peptic ulcer haemorrhage was similar to that recently reported in a large district general hospital (Katschinski et al, 1989). However, in the study conducted by Katschinski and co-workers (1989) the observed mortality of approximately 10% associated with peptic ulcer haemorrhage fell to about 5% when only death directly associated with bleeding was considered.…”
Section: Discussioncontrasting
confidence: 37%
“…Although changes in the distribution and rates of peptic ulceration have been noted over the last three decades (Coggan et al, 1981) mortality is still significant with recent studies providing estimates of about 5% in patients with peptic ulcer haemorrhage (Daneshmend et al, 1992;Holman et al, 1990;Katschinski et al, 1989;Walt et al, 1991). However, a relative increase in the incidence of gastrointestinal haemorrhage has also been demonstrated in the elderly (Bardhan et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…4 patients were lost to follow up. In a study conducted by Katschinski et al 29 , death occurred in 189 (8.5%) patients, and 243 (11%) patients experienced rebleeding. Zaltmanet al 30 showed Rebleeding in 9.1% of the patients and overall mortality rate of 15.34%.…”
Section: Resultsmentioning
confidence: 99%
“…Approximately 30,000 people are admitted to hospital each year in the U.K. with upper G I bleeding ranging across a broad spectrum. About 20°4, of these require surgery, and the death rate is approximately 10% (134).…”
Section: Stress Bleedingmentioning
confidence: 99%